2017
DOI: 10.1186/s12889-017-4263-2
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the role of Community Health Representatives in the Navajo Nation

Abstract: BackgroundStrengthening Community Health Worker systems has been recognized to improve access to chronic disease prevention and management efforts in low-resource communities. The Community Outreach and Patient Empowerment (COPE) Program is a Native non-profit organization with formal partnerships with both the Navajo Nation Community Health Representative (CHR) Program and the clinical facilities serving the Navajo Nation. COPE works to better integrate CHRs into the local health care system through training,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 8 publications
0
39
0
7
Order By: Relevance
“…At the patient level, we have described how patient selfefficacy is strengthened through emotional support, health coaching, and navigation support from CHRs to access care such as appointments and medication refills [22]. At the provider level, we have described how the intervention enhances CHRs' ability to deliver standardized, evidence-based, culturally-tailored outreach to their patients and communicate more effectively with clinic providers about patient issues [23]. At the system level, we have demonstrated that the intervention strengthens community-clinic linkages, validating CHRs as members of the care team and increasing care coordination among clinic providers and CHRs [24].…”
Section: Discussionmentioning
confidence: 99%
“…At the patient level, we have described how patient selfefficacy is strengthened through emotional support, health coaching, and navigation support from CHRs to access care such as appointments and medication refills [22]. At the provider level, we have described how the intervention enhances CHRs' ability to deliver standardized, evidence-based, culturally-tailored outreach to their patients and communicate more effectively with clinic providers about patient issues [23]. At the system level, we have demonstrated that the intervention strengthens community-clinic linkages, validating CHRs as members of the care team and increasing care coordination among clinic providers and CHRs [24].…”
Section: Discussionmentioning
confidence: 99%
“…As part of an ongoing program evaluation by COPE, deidentified data were extracted from the IHS electronic health record for all patient encounters on the reservation from 2009 to 2016 with a DM Audit Problem Diabetes Diagnosis taxonomy, which includes ICD-9 and ICD-10 codes for diabetes mellitus [18]. Permission to access health data was given by the Navajo Area IHS, and this project was approved by the Navajo Nation Human Research Review Board and the Partners Healthcare Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Navajo CHRs are required to be trained as a Certified Nursing Assistant (CNA) and must speak Navajo. Many CHRs have additionally obtained certification and credentialing beyond the CNA required for the job, including CHW certification through the state of New Mexico 21. Typical services provided by Navajo CHRs include home visits to monitor vital signs and provide health education, referrals for additional services and resources needed by their client, community outreach for urgent or emergent issues, and health fairs and other health promotion activities.…”
Section: Methodsmentioning
confidence: 99%
“…Specific templates were created for providers to make referrals to CHRs and for CHRs to document their home visits. Improvements in communication were shown as a result of this system change 21…”
Section: Methodsmentioning
confidence: 99%